A Case of Adjacent, Clonally Distinct Borderline Melanocytic Tumors on the Arm. (January 2020) - Schuler, Andrew; Smith, Mallory; Zahn, Joseph; Wang, Min; Noh, Iris; Chan, May P.; Andea, Aleodor A.; Harms, Paul W.
Abstract : Abstract: Atypical Spitz tumor (AST) is a melanocytic proliferation that shares histopathologic features of Spitz nevus and spitzoid melanoma. Distinction of AST from spitzoid melanoma is critical because the majority of ASTs will follow an indolent course. Array-based comparative genomic hybridization (aCGH) has been suggested as a potential tool for evaluating malignant potential in spitzoid tumors. We present a case of a 52-year-old woman with an AST in which aCGH was crucial in guiding correct diagnosis and management. The patient first presented with a flesh-colored papule on her arm that was changing color. Biopsy revealed a dermal nevoid melanocytic tumor of indeterminate histopathology, favored to be a severely atypical nevus. The tumor was excised. One year later, another flesh-colored papule proximal to the excision site of the first tumor was biopsied and showed a predominantly dermal atypical spitzoid melanocytic proliferation with a differential diagnosis of AST versus spitzoid melanoma. Recurrent or metastatic melanoma was also a concern given proximity to the previous excision site. Molecular analysis of both lesions by aCGH revealed distinct molecular signatures, supporting the 2 tumors to be clonally unrelated. Furthermore, the new tumor displayed limited evidence of genomic instability, supporting classification as an AST with predicted indolent behavior. This case highlights the utility of aCGH in evaluating borderline melanocytic lesions, including assessment of malignant potential in ASTs, and clonality analysis to assist in exclusion of metastatic disease.